2021
DOI: 10.1017/s0031182021000755
|View full text |Cite
|
Sign up to set email alerts
|

The situation of echinococcosis in stray dogs in Turkey: the first finding of Echinococcus multilocularis and Echinococcus ortleppi

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 72 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…Phylogenetic analysis revealed that the two EG isolates detected as belonging to the G6/7 genotype were 100% identical with previously identified G6/7 isolates in humans in other regions of Pakistan (MK229300 and MK229305) [ 29 ]. In addition, they were similar to the G6/7 isolates identified in camel, dog, and pig isolates in Kazakhstan, Turkey, and Japan [ 40 , 41 ], which suggests that a common G6/7 genotype of EG may be circulating in humans, dogs, and other intermediate hosts in Pakistan and other countries in Asia. Evolutionary analysis revealed that G1 and G3 isolates in this study were related to, but somewhat diverse from, already reported isolates in humans, buffalo, and sheep from other regions of Pakistan [ 18 , 29 ], as well as those reported in China, Italy, and Mongolia [ 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 63%
“…Phylogenetic analysis revealed that the two EG isolates detected as belonging to the G6/7 genotype were 100% identical with previously identified G6/7 isolates in humans in other regions of Pakistan (MK229300 and MK229305) [ 29 ]. In addition, they were similar to the G6/7 isolates identified in camel, dog, and pig isolates in Kazakhstan, Turkey, and Japan [ 40 , 41 ], which suggests that a common G6/7 genotype of EG may be circulating in humans, dogs, and other intermediate hosts in Pakistan and other countries in Asia. Evolutionary analysis revealed that G1 and G3 isolates in this study were related to, but somewhat diverse from, already reported isolates in humans, buffalo, and sheep from other regions of Pakistan [ 18 , 29 ], as well as those reported in China, Italy, and Mongolia [ 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 63%
“…AE is a major public health concern in the country, particularly prevalent in rural areas located in the eastern regions [27]. There are available data on the presence and prevalence of E. multilocularis in the nal hosts of Erzurum province: 10.5-42% in foxes [28], 3.6-8.3% in dogs [25,29] and in a lynx [30] were presented. In addition, E. multilocularis was detected in stray dogs (8.7%) in a regional study covering the entire northeastern region of Turkey [29].…”
Section: Resultsmentioning
confidence: 99%
“…The existence of E. granulosus in Kazakhstan, E. intermedius (G7) in Portugal, E. granulosus and E. multilocularis in Italy, and E. canadensis / E. multilocularis mix infections in wolves have been recorded in Canada and Mongolia ( Guberti et al, 2004 ; Abdybekova and Torgerson, 2012 ; Guerra et al, 2013 ; Ito et al, 2013 ; Schurer et al, 2014 ; Massolo et al, 2018 ). Now, E. granulosus s.s. , E. equinus, E. ortleppi , E. canadensis (G6/G7) and E. multilocularis circulate in human and animals in Turkey ( Inceboz et al, 2005 ; Avcioglu et al, 2016 , 2021 ; Kesik et al, 2020 ). E. canadensis (G6/7) has been reported in sheep, cattle, and humans ( Mehmood et al, 2020 ; Bakal et al, 2021 ; Kesik et al, 2021 ), while E. equinus has been found in donkeys, mules and humans in some previous studies in Turkey ( Simsek and Cevik, 2014 ; Kesik et al, 2019 ; Macin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%